Arts-based methods in leadership education – a cluster analysis from Northern Africa - Kriek, Hendrik Sebastiaan; Fritzsche, Albrecht (Strategy and Leadership, 2025)
Purpose Arts can be used in many different ways in leadership education. This paper explores how students perceive four different arts-based approaches: (1) design/ visual interpretation, (2) object construction, (3) practical theatre exercises, and (4) practical dance exercises. Design/methodology/approach Data were collected using a questionnaire distributed among students at a business school in Morocco. Students were asked about their perception of arts-based methods in leadership education and different learning objectives that can be achieved. The resulting dataset was subjected to a cluster analysis. Findings The analysis unveils four distinct patterns in which students respond to arts-based methods. For a majority of the students, arts-based methods are welcome, but there is also a small fraction of students who are consistently critical about them. Furthermore, the clusters allow distinctions between preferences for different arts and varying expectations regarding the learning objectives. Originality/value The study lays the groundwork for a typology of different target groups that need to be taken into account in planning the use of arts-based methods in class. It enables leadership education to apply such methods more effectively, respecting diverse preferences and abilities of learners when designing course
Keywords: Design; Cluster Analysis